Prediksi Sebaran Parameter Polutan Air Limbah pada Upstream dan Downstream Sungai Area Industri X Mojokerto - Tuhu Agung Rachmanto; Muhammad Dani Dhaifullah (Prosiding ESEC, 2023)
The Gembolo River is ± 14-15 m wide with a depth of 1 to 2 m and flows towards the north (downstream). With the movement of river water flow, there will be an influence in the direction of the movement of the river flow. The distribution of pollutant parameters due to the movement of the river flow will result in a decrease in pollutant concentrations along with the further movement of the water flow of the water body (self-purification). This study aims to determine the simulation of decreasing the concentration of key parameters from the resulting treated wastewater, including BOD, COD, TSS, ammonia (NH4) and total coliform in the Gembolo River, Mojokerto. The simulation itself was carried out for 15 days taking into account seasonal conditions (dry season and rainy season) with the help of Mike 21 software. The results of the simulation along the Gembolo River during the dry season and rainy season have different results, namely a BOD of 1.02 mg /l and 0.980 mg/l, COD of 1.4 mg/l and 1.23 mg/l,and ammonia (NH4) of 0.386 mg/l and 0.381 mg/l. From the simulation, when compared with the required quality standard, it is still below the quality standard.